2011
DOI: 10.1186/1471-244x-11-164
|View full text |Cite
|
Sign up to set email alerts
|

Sub-threshold depression and antidepressants use in a community sample: searching anxiety and finding bipolar disorder

Abstract: BackgroundTo determine the use of antidepressants (ADs) in people with sub-threshold depression (SD); the lifetime prevalence of mania and hypomania in SD and the link between ADs use, bipolarity and anxiety disorders in SD.MethodsStudy design: community survey. Study population: samples randomly drawn, after stratification from the adult population of municipal records. Sample size: 4999 people from seven areas within six Italian regions. Tools: Questionnaire on psychotropic drug consumption, prescription; St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
0
17
0
2
Order By: Relevance
“…However, in the broad spectrum of mood and anxiety disorders, there are different disorders requiring even different treatments. Although many antidepressants are also indicated in anxiety disorders, they are rarely used in anxiety disorders not associated with depression in Italy [29]. …”
Section: Discussionmentioning
confidence: 99%
“…However, in the broad spectrum of mood and anxiety disorders, there are different disorders requiring even different treatments. Although many antidepressants are also indicated in anxiety disorders, they are rarely used in anxiety disorders not associated with depression in Italy [29]. …”
Section: Discussionmentioning
confidence: 99%
“…Panic attack anxiety disorder is highly comorbid with type II bipolar disorder, and it has been suggested that the clinical manifestations of the panic attack is an expression of hyperthymia, specifically the “anxious hyperthymia”; this is a possible personality pre-morbid trait in panic disorder [71]. Both major depression and panic disorder are strongly bound to bipolar disorder, in terms of comorbidity [72], familiarity [73] and in a purported syndromic continuum with major depressive disturbance [74,75]. …”
Section: Introductionmentioning
confidence: 99%
“…Since it is very difficult to identify bipolar depression and, more generally, to diagnose bipolar disorders [31, 32], the use of antidepressants in a non-psychiatric setting and with non-psychiatric indications in patients at high risk of bipolar disorder, as are the patients with fibromyalgia, could increase the non-recognition of bipolar disorder and, therefore, the inappropriate use of antidepressants. An antidepressant treatment without stabilizers in a bipolar disorder can worsen the course of the illness due to the poor response to the depressive symptoms, and even worsen the mania components [4,5].…”
Section: Discussionmentioning
confidence: 99%